Differences in MEG gamma oscillatory power during performance of a prosaccade task in adolescents with FASD - Stephen, Julia M.; Coffman, Brian A.; Stone, David; Kodituwakku, Piyadasa (Frontiers in Human Neuroscience, 2013)
Fetal alcohol spectrum disorder (FASD) is characterized by a broad range of behavioral and cognitive deficits that impact the long-term quality of life for affected individuals. However, the underlying changes in brain structure and function associated with these cognitive impairments are not well understood. Previous studies identified deficits in behavioral performance of prosaccade tasks in children with FASD. In this study, we investigated group differences in gamma oscillations in response to a prosaccade task. We collected MEG data from 15 adolescents with FASD and 20 age-matched healthy controls (HC) with a mean age of 15.9 ± 0.4 years. During the prosaccade task, the participants began each trial by gazing at a centrally-placed fixation point. After a variable delay, a peripheral target appeared along the horizontal meridian in left or right visual field. The participants were instructed to saccade to the target as quickly and accurately as possible. Eye movement was recorded and synchronized to the MEG data using an MEG compatible eye-tracker. The MEG data were analyzed relative to the onset of the visual saccade. Time frequency analysis was performed using Fieldtrip with a focus on group differences in gamma-band oscillations. Following left target presentation, we identified 4 clusters over right frontal, right parietal and left temporal/occipital cortex, with significantly different gamma-band (30-50 Hz) power between FASD and HC. Furthermore, visual M100 latencies described in Coffman et al. (2012) corresponded with increased gamma power over right central cortex in FASD only, which may represent compensatory activity in this group. Gamma-band differences were not identified for stimulus-averaged responses implying that these gamma-band differences were related to differences in saccade network functioning. These gamma-band differences in power may provide indicators of atypical development of cortical networks in individuals with FASD.